Green innovation in corporate social responsibility in Peruvian coffee organizations - Avalos Millones, Myriam; Rivera Barrios, Angie Paola; Montes Tocto, Richard Ignacio; Collazos Alarcón, Mercedes Alejandrina (LACCEI, 2025)
The purpose of this research is to evaluate green innovations in the framework of corporate social responsibility (CSR) in four Peruvian coffee organizations. Using a quantitative method and a transversal, non-experimental design, we applied a 5-point Likert scale survey, yielding a total of 80 responses. The objective of this analysis was to determine the characteristics of green innovation in the organizations. The results show that 58.75% of the organizations achieve high levels of green innovation, and 66.3% achieve outstanding social results. However, 67.5% present regular corporate images, highlighting opportunities to strengthen sustainability and positive impact. Overall, the study highlights that, although coffee organizations are moving towards greater adoption of green innovations and sustainable practices, there are still areas for improvement, especially in terms of corporate image. These results provide valuable information to develop strategies and improve sustainability and social responsibility in the coffee industry.